丹戎布拉大学师范教育学院汉语教育专业 2017 届学生对介词 “对于”与“关于”的掌握情况分析 - Nurjannah Nurjannah; Lily Thamrin; Suhardi Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract"Duiyu" and "guanyu" are two types of propositions that both indicate an object and are frequently used in everyday conversation. Both have similarities and differences, so students frequently use them incorrectly. As a result, the authors used the test method on students to determine the level of mastery and difficulty of the prepositions "duiyu" and "guanyu" in 2017 among students of the Mandarin Language Education Study Program, Teacher Training and Education Faculty, Tanjungpura University. The finding showed that, while studying these two words, there were types of usage that students had mastered well, as well as types of usage that had not been so mastered. On the word "duiyu," the correct percentage for class A is 55.0 percent, and 48.6 percent for class B. In the case of the word "guanyu," the percentage for class A is 56.2 percent and for class B is 52.1 percent.Keywords: preposition word “duiyu” “guanyu” Using analysis